A Ni-based catalyst with enhanced Ni–support interaction for highly efficient CO methanation. Issue 14 (17th May 2018) - Yan, Xiaoliang; Yuan, Chen; Bao, Jiehua; Li, Sha; Qi, Daizong; Wang, Qianqian; Zhao, Binran; Hu, Tong; Fan, Liming; Fan, Binbin; Li, Ruifeng; Tao, Franklin (Feng); et al.
Abstract : A Ni/NiAl2 O4 catalyst with an enhanced Ni–support interaction was successfully fabricated for highly efficient CO methanation. Abstract : Sophisticated manipulation of the metal–support interaction of catalysts is of great importance for achieving a higher catalytic efficiency, but remains as an open challenge. Herein, by using a simple metal–organic framework (MOF) based strategy, a Ni/NiAl2 O4 –M catalyst with an enhanced Ni–support interaction is successfully fabricated. The catalyst exhibits an enhanced low-temperature catalytic performance in CO methanation. CO conversion and CH4 selectivity as high as 99.8% and 58.0%, respectively, are achieved on the Ni/NiAl2 O4 –M catalyst at 350 °C. The strong Ni–support interaction on the Ni/NiAl2 O4 –M catalyst results in more active H atoms, and promotes the formation of active CH* species which are the key intermediates for CO methanation. This not only enhances the conversion of CO into CH4, but also suppresses the carbon deposition which has a negative effect on the catalytic reactions, thus improving the catalytic performance of Ni/NiAl2 O4 –M. Besides, the strong Ni–support interaction makes Ni/NiAl2 O4 –M highly resistant to sintering of the Ni nanoparticles during the catalytic reactions. The findings of the present work are helpful for fabricating catalysts with enhanced metal–support interaction for more efficient catalysis.